Reformimg the stability and growth pact: Flexible deficit rules but limits on public debt - Ognian N. Hishow (Stiftung Wissenschaft und Politik (SWP), 2005)
In its present form, the Stability and Growth Pact runs counter to its intended effect, since it tends to encourage debt especially in slow-growing economies. This is because of a design fault: very few states simultaneously comply with the 3% ceiling for the budget deficit and the 60% limit for the public debt as witnessed by the actual growth rates and debt ratio in the EU. For this reason the recommended policy would be to retain only the 'debt ratio' reference value (60% of GDP). Instead of the rigid 3% rate for maximum new borrowing, the proposed alternative rule would take growth and total public debt into account. (SWP Comments / SWP)
Keywords: 320